2016
DOI: 10.1021/acs.jpcc.6b03146
|View full text |Cite
|
Sign up to set email alerts
|

Surface Charge Layer of Amorphous Solid Water with Adsorbed Acid or Base: Asymmetric Depth Distributions of H+ and OH Ions

Abstract: The charge at the surface of water and the resultant surface voltage play an important role in many natural phenomena and technological applications. However, the relationship between surface charge and the interfacial distribution of H + and OH − ions remains unclear. We measured the surface voltage produced by an ionized acid or a base at the surface of amorphous solid water (ASW) using a Kelvin work-function probe and studied the depth distributions of H + and OH − ions. H + ions were distributed over a thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…However, the hydronium ions could undergo thermal diffusion and accumulate at the surface of a growing ASW film at high temperature because of their thermodynamic affinity for the ice surface. ,, For this reason, the possibility of upward diffusion of hydronium ions at 80 K was worth investigating. The necessary information could be obtained from the measurement of the surface voltages of HCl-doped ASW films, as described by Lee et al An analysis of the changes in the film voltage with the growth of the ASW overlayer on the HCl-adsorbed ASW surface at 95 K (Figure 5 in ref ) showed that the average penetration depth of excess protons into the ASW overlayer was 3.5 ML when the HCl adsorbate coverage was 0.04 ML. This penetration depth decreased with an increase in HCl coverage, probably as a result of electrostatic interactions between H + and Cl – ions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the hydronium ions could undergo thermal diffusion and accumulate at the surface of a growing ASW film at high temperature because of their thermodynamic affinity for the ice surface. ,, For this reason, the possibility of upward diffusion of hydronium ions at 80 K was worth investigating. The necessary information could be obtained from the measurement of the surface voltages of HCl-doped ASW films, as described by Lee et al An analysis of the changes in the film voltage with the growth of the ASW overlayer on the HCl-adsorbed ASW surface at 95 K (Figure 5 in ref ) showed that the average penetration depth of excess protons into the ASW overlayer was 3.5 ML when the HCl adsorbate coverage was 0.04 ML. This penetration depth decreased with an increase in HCl coverage, probably as a result of electrostatic interactions between H + and Cl – ions.…”
Section: Discussionmentioning
confidence: 99%
“…The mobility of excess protons (positive protonic defects) in ice is intimately related to the diverse physical , and chemical properties of ice . The general concept of proton transport in ice was originally formulated by Jaccard , and Onsager and is now well accepted through extensive experimental verification. The excess protons in ice move along its hydrogen-bonded network via an efficient hopping relay (Grotthuss) mechanism. , The proton passage along the hydrogen-bonded water chain polarizes the direction of the hydrogen bonds, which blocks the passage of the subsequent protons hopping along the same path. Therefore, for a continuous flow of protons, reorientation of water molecules (Bjerrum defect motion) must take place to depolarize the hydrogen-bond direction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations